2018
DOI: 10.1159/000492819
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Trends of Multiple Sclerosis Disability-Adjusted Life Years Rates: A 25-Year Assessment

Abstract: Background: Multiple sclerosis (MS) burden of disease has been described by reporting the disability-adjusted life years (DALY) index. So far, no study has assessed the trend of MS DALY rates over time. Method: Age-standardized MS DALY rates for both sexes were reported every 5 years from 1990 to 2015 in 195 countries in the Global Burden of Disease Database (GBD) database. To assess the MS DALY rates’ trends in each super region and throughout the world, we applied the Latent Growth Models. We also utilized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In spite of the low incidence and prevalence rates, MS is one of the leading causes of non-traumatic disability in young adults (World Health Organization [WHO] 2013). Interestingly, the global MS burden of disease, assessed by disabilityadjusted life years (DALY), has been recently reported to have a global downward trend 43 . This trend was found for both developed and developing countries, although MS DALY rates are about 25 higher in developed countries compared to developing ones.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the low incidence and prevalence rates, MS is one of the leading causes of non-traumatic disability in young adults (World Health Organization [WHO] 2013). Interestingly, the global MS burden of disease, assessed by disabilityadjusted life years (DALY), has been recently reported to have a global downward trend 43 . This trend was found for both developed and developing countries, although MS DALY rates are about 25 higher in developed countries compared to developing ones.…”
Section: Discussionmentioning
confidence: 99%
“…Other similar studies have also shown a higher incidence rate of MS at an early age [7,40]. The disease onset in the early age leads to an increase in the number of years lived with disability (YLDs) and eventually to disability-adjusted life years (DALYs) [4,41,42].…”
Section: Discussionmentioning
confidence: 89%
“…The disease Fig. 1 The age-standardized sex ratio (female to male) of MS, Tehran, Iran, 2006-2018 onset in the early age leads to an increase in the number of years lived with disability (YLDs) and eventually to disability-adjusted life years (DALYs) [4,40,41].…”
Section: Discussionmentioning
confidence: 99%